Modes of griot inscription in African cinema. (1st March 2016) - Fisher, Alexander
A recurring idea in the criticism of African cinema has been that the films frequently deploy the narrative techniques of the griot, the storyteller of West African tradition. In particular, Manthia Diawara (1989, 1992) alerted us to the inscription of the oral narrator within the visual discourse of particular African films, while other critics have considered how the films recall the narrative forms of traditional oral tales. However, these critics' exclusive attention to the visual track and/or narrative form overlooks another inscription of the griot – an inscription that exists at the level of music. Examining music and image relationships in an aesthetically diverse set of African films, this article demonstrates how griot inscription emerges as a major variable, modulating between music and image within and between texts. This propels music, and the griot, to a status of primary importance in terms of understanding the ways in which the films explore and reappropriate notions of 'African-ness' while negotiating the tensions of address generated when oral forms of narrative meet the industrial form of cinema.